Clonal nature of enterotoxigenic Escherichia coli serotype O6 : H16 revealed by randomly amplified polymorphic DNA analysis - Pacheco, Ana B. F. (1998)
Fil: Pacheco, Ana B. F. Universidade Federal do Rio de Janeiro. Instituto de Biofisica Carlos Chagas Filho; Brasil.